Antifungal Activity of Gelatin-Tapioca Starch Film and Coating Containing Copper Nanoparticles against Colletotrichum gloeosporioides Causing Anthracnose - Vinh Tien Nguyen; My-Sam Dang-Thi; Khanh Son Trinh (Journal of Chemistry)
This study aimed to fabricate a nontoxic coating containing copper nanoparticles (CuNPs) to protect fruits from pathogenic Colletotrichum gloeosporioides causing anthracnose on several tropical fruits. We used a green approach, in which CuNPs were synthesized by reducing CuSO4 with ascorbic acid in the presence of gelatin and glycerol as the capping agents. The formation of CuNPs was confirmed by UV-vis absorption spectra of the reaction mixture, which showed a surface plasmon resonance peak at 578–594 nm. The x-ray diffraction spectrum of the CuNPs indicated the presence of mostly metallic copper with some minor impurities of Cu2O, CuO, and Cu(OH)2. Transmission electron microscopy (TEM) images and dynamic light scattering studies showed that the sizes of 90% of CuNPs were in 100–300 nm range. A 30–50 nm capping layer of gelatin surrounding CuNPs can be observed in the TEM images. Comparing FTIR spectra of the used reagents and CuNPs confirmed the depletion of ascorbic acid, as well as the gelatin layer protecting CuNPs. The synthesized CuNPs showed dose-dependent antifungal activity against C. gloeosporioides with 100% growth inhibition at 200 ppm copper. Gelatinized tapioca starch was then added to the CuNPs solution to obtain a film-forming mixture to produce stand-alone composite films on Petri dishes and coatings on mangoes. C. gloeosporioides could not grow on the surface of nutrient agar in contact with the films containing 245 ppm CuNPs, while they grew normally on control films without CuNPs. For the in vivo antifungal tests on mangoes, both the control and the CuNPs-containing coatings equally inhibit fungal growth, possibly due to the low oxygen permeability of the protein and starch components in the films. This study thus demonstrated the potential applications of composite coatings using biodegradable polymers that contain CuNPs in postharvest protecting fruits from phytopathogenic fungi.